The impact of seed vouchers on poverty reduction among smallholder rice farmers in Nigeria - Awotide, B.A.; Karimov, A.; Diagne, A.; Nakelse, T. (Wiley, 2013)
In response to the global food crisis of 2008, the United States Agency for International Development (USAID) funded an emergency rice initiative (ERI) program to boost rice production in Nigeria. The supplementary seed voucher program, implemented alongside the ERI adopted a randomized control trial to grant randomly selected farmers access to subsidized certified improved rice seed using the seed voucher system (SVS). In this study, we provide a consistent estimate of the impact of the SVS on Poverty reduction, using mixed methodologies such as inverse propensity score weighing (IPSW) and the local average treatment effect (LATE) estimation techniques. Results show that the SVS has a positive and statistically significant impact on annual household income and per capita consumption expenditure. This study shows that availability of good quality seed at an affordable price can raise agricultural productivity, increase household income and contribute to poverty reduction.